Potensi Implementasi Pembelajaran Berdiferensiasi Berorientasi ESD dalam Projek IPAS Aspek Zat dan Perubahannya - Latifah, Nur; Hayat, Muhammad Syaipul; Khoiri, Nur (Jurnal Penelitian Pembelajaran Fisika, 2023)
This study aims to analyze the potential implementation of ESD-oriented differentiated learning (Education for Sustainable Development) in the IPAS Project, aspects of substances and their changes. This research is a type of qualitative descriptive research. Interview, survey and documentation methods were chosen as data collection techniques. The results of the data collection were analyzed using data triangulation. 26 teachers of the Science Project in Jepara Regency were randomly selected as respondents. From the survey results, 88% understood and implemented differentiated learning in the IPAS Project, aspects of substances and their changes. However, there are 77% of teachers consider the implementation of differentiated learning to take a lot of time so that the available lesson hours are insufficient, 65% consider the implementation of differentiated learning very troublesome for teachers because there are many stages to do, 65% already understand the concept of ESD-oriented learning in the IPAS Project, 85% of teachers use waste items or simple tools obtained in the surrounding environment in substance learning and the changes. In addition, 96% of students are able to utilize unused used items into practice materials for substance and change projects, and 88% of teachers stated that learning aspects of substances and changes is ESD-oriented able to instill the value of attitudes, appearance and awareness of paying attention to life for the next generation. Another fact based on interviews found that some teachers do not implement a differentiated learning approach due to the difficulty of making teaching modules and LKPD.